AKTUALISASI SILA KE-5 PANCASILA UNTUK MENGATASI MASALAH KEMISKINAN DI INDONESIA - Olfiyani, Geni Aufana; Ulfatun Najicha, Fatma (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2022)
Poverty is a phenomenon in which a person is deficient in meeting his life needs. There are many factors that cause poverty, including differences in the quality of existing human resources, differences in access to various life facilities, disasters such as disease outbreaks, natural disasters, and so on. The form of settlement of poverty cases is implementing and implementing the values ​​contained in the Pancasila precepts, especially the fifth Pancasila precept. This research uses a descriptive approach method, namely library research. Literature study is a process of studying and analyzing more deeply about data, facts, theories, and concepts. The object that forms the basis for writing this article is the Indonesian people, especially those who are still experiencing poverty. The author chose the object in this study because the author wants to raise awareness to all parties that Indonesian people need to get proper welfare and livelihood.